DUKUNGAN TEMAN SEJAWAT DI JEJARING SOSIAL DALAM PEMBERIAN ASI EKSKLUSIF - Linda Puji Astutik (Jurnal Medika : Karya Ilmiah Kesehatan, 2018)
The health beneﬁts of breastfeeding are enhanced when exclusive breastfeeding is maintained for six months. Discontinuing with breastfeeding over the early weeks make unsuccessfull exclusive breastfeeding so that the baby does not get benefit from exclusive breastfeeding. Many factors influence exclusive breastfeeding, one of which is support from peers. Mother's busyness makes mothers limited in socializing so it needs support from network partners. This study aims to find a network of peer relations with the success of exclusive breastfeeding. this study uses cross sectional methods with online survey for mother who have baby between 6-12 month who are member of AIMI JATIM grup in social network. This research will produce findings of relation between peer support in social networh with exclusve breastfeeding. This study is expected to find correlation between network peer support and exclusive breastfeeding.